Use of soil nematodes as indicators of soil and plant health in continuous cropping systems: A case study in dragon fruit - Zhechao Dou; Jing Ma; Kunguang Wang; Qiaofang Lu; Zhiguang Chi; Dongming Cui; Chang Pan; Zhuchi He; Yuanmei Zuo (Journal of Integrative Agriculture)
Crops produced using the practice of continuous cropping can become seriously damaged by plant-parasitic nematodes, an important indicator of continuous cropping obstacles. As a typical and important perennial economic crop, dragon fruit is prone to serious plant-parasitic nematode infestation; however, whether it encounters continuous cropping obstacles remains unclear. Here, we studied plant-parasitic nematodes (Meloidogyne spp. and Tylenchorhynchus sp.) in the soil and roots, soil nematode communities, metabolic footprint, soil integrated fertility, and the yield of intensively planted dragon fruit under non-continuous cropping (Y1) and 3 years (Y3) and 5 years (Y5) of continuous cropping, to determine potential continuous-cropping obstacles and factors that affect the yield of this fruit. The largest numbers of plant-parasitic nematodes in the soil and roots were observed in Y5; the associated yield was reduced, and the dragon fruit was severely stressed. Further analysis of the composition, diversity, and ecological function indices of soil nematodes showed that the soil ecological environment deteriorated after 3 years of continuous cropping, with Y5 having the worst results. Similarly, the soil at Y5 had a significant inhibitory effect on the growth and reproduction of Caenorhabditis elegans. Mantel test analysis and a random forest model showed that soil available phosphorus, soil exchange calcium, and soil nematode abundance and diversity were related significantly to yield. Partial least squares path modeling revealed that soil fertility and soil nematode diversity directly impacts the yield of continuously cropped dragon fruit. In summary, continuous cropping obstacles occurred in Y5 of intensive dragon fruit cultivation, with soil nematode diversity and soil fertility determining the crop’s yield.